Plasticity of fruit and oil traits in olive among diferent environments - Mousavi, Soraya; De la Rosa, Raúl; Moukhli, Abdelmajid; El Riachy, Milad; Mariotti, Roberto; Torres, Myriam Mariela; Pierantozzi, Pierluigi; Stanzione, Vitale; Mastio, Valerio; Zaher, Hayat; El Antari, Abderraouf; Ayoub, Salam; et al. (Springer Nature, 2021)
Olive is a long-living perennial species with a wide geographical distribution, showing a large genetic and phenotypic variation in its growing area. There is an urgent need to uncover how olive phenotypic traits and plasticity can change regardless of the genetic background. A two-year study was conducted, based on the analysis of fruit and oil traits of 113 cultivars from fve germplasm collections established in Mediterranean Basin countries and Argentina. Fruit and oil traits plasticity, broad‐sense heritability and genotype by environment interaction were estimated. From variance and heritability analyses, it was shown that fruit fresh weight was mainly under genetic control, whereas oleic/(palmitic+linoleic) acids ratio was regulated by the environment and genotype by environment interaction had the major efect on oil content. Among the studied cultivars, diferent level of stability was observed, which allowed ranking the cultivars based on their plasticity for oil traits. High thermal amplitude, the diference of low and high year values of temperature, negatively afected the oil content and the oleic acid percentage. Information derived from this work will help to direct the selection of cultivars with the highest global ftness averaged over the environments rather than the highest ftness in each environment separately.